Hemolymph Proteomics and Gut Microbiota of Horseshoe Crabs Tachypleus tridentatus and Carcinoscorpius rotundicauda - Qu, Zhe; Leung, Thomas C. N.; Nong, Wenyan; Yip, Ho Yin; Lee, Ivy H. T.; Cheung, Siu Gin; Ming, Ngai Sai; So, Wai Lok; Bendena, William G.; Tobe, Stephen S.; Hui, Jerome H. L. (Frontiers in Marine Science, 2020)
Horseshoe crabs are a group of marine chelicerates that contain only four extant species, and some of which become endangered. Their hemolymph has been widely used in medical applications for endotoxins detection. Nevertheless, there are only limited information on the profiles of their hemolymph proteins and gut microbiota diversity. In this study, we performed the first detailed investigation of the hemolymph proteomics and gut microbiota of two Asian horseshoe crabs Tachypleus tridentatus and Carcinoscorpius rotundicauda. Among the identified proteins being catalogued in the juvenile and adult hemolymph, unexpectedly, sesquiterpenoids signaling pathway proteins including Heat shock protein 83 (HSP83), Chd64 and a juvenile hormone binding protein (JHBP) were revealed. This provides evidence for the presence of functional sesquiterpenoid hormonal systems in these marine chelicerates. Consumption of horseshoe crabs often leads to tetrodotoxin poisoning and the horseshoe crab is thought to possess a tetrodoxin resistance mechanism. As such, sodium channels were analysed and found to have critical amino acid residues that are similar to the toxin resistant pufferfish sodium channels. The source of the toxin is unknown so we investigated the gut microbiota, and found that Clostridium and Vibrio were the most dominant bacteria in T. tridentatus and C. rotundicauda, respectively. Together, this study provides a framework for further understanding of sesquiterpenoids and gut microbiota of these marine chelicerates.